Dietary intake of branched-chain amino acids and pancreatic cancer risk in a case–control study from Italy. Issue 9 (14th May 2023) - Turati, Federica; Rossi, Marta; Strikoudi, Panagiota; Ferraroni, Monica; Parpinel, Maria; Serraino, Diego; Negri, Eva; La Vecchia, Carlo
Abstract: Circulating branched-chain amino acids (BCAA), a subgroup of the nine essential amino acids, has been associated with pancreatic cancer risk. The aim of this study is to estimate the relation between BCAA intake from diet and pancreatic cancer risk. We analysed data from a multicentric Italian case–control study, including 326 pancreatic cancer cases and 652 controls, matched to cases by study centre, sex and age. A validated FFQ was used to collect the participants' usual diet before cancer diagnosis (or hospital admission for controls) and to compute dietary intakes of various nutrients, including BCAA. OR and the corresponding CI were computed through logistic regression models conditioned on the matching variables and adjusted for major confounding factors, including total energy intake. We found a positive association between BCAA intake and pancreatic cancer risk (OR for the third quartile = 1·88, 95 % CI = 1·08, 3·26; OR for the fourth quartile = 2·17, 95 % CI = 1·17, 4·06), with a significant trend in risk. The association persisted after excluding subjects with diabetes and family history of pancreatic cancer and across strata of selected covariates. These data support and quantify the association between dietary BCAA and pancreatic cancer, previously suggested by studies on circulating BCAA.